Electron–electron interactions and the paired-to-nematic quantum phase transition in the second Landau level - K. A. Schreiber (Nature Portfolio, 2018)
Two-dimensional electron systems at half-filled Landau levels can form unusual electronic states such as paired fractional quantum Hall and nematic phases. Here the authors observe the transition between these two phases at filling factors 5/2 and 7/2 and demonstrate the important influence of interactions.